Intent-to-cure surgery for small-cell lung cancer in the era of contemporary screening and staging methods. (9th January 2020) - Chenesseau, Joséphine; Bourlard, Donatienne; Cluzel, Armand; Trousse, Delphine; D'Journo, Xavier-Benoît; Thomas, Pascal Alexandre
Abstract: : OBJECTIVES: Our goal was to report on the contemporaneous single-centre experience of patients with small-cell lung cancer (SCLC) who had lung resection with curative intent. METHODS: Between 2005 and 2018, 31 patients were operated on for SCLC with curative intent. There were 11 women and 20 men whose ages averaged 63 ± 10 years. The clinical diagnosis was incidental in 16 patients (51.6%). All patients were screened with high-resolution computed tomography, positron emission tomography and brain imaging. Eight patients (25.8%) had invasive mediastinal lymph node staging. RESULTS: Preoperative tissue diagnosis was unknown or erroneous in 26 patients (83.9%). Lung resections comprised mainly lobectomies ( n  = 23; 74.2%). Lymphadenectomies harvested a mean of 16.3 ± 3 lymph nodes, leading to upstaging in 38.7% of the cases. An R0 resection was achieved in 28 patients (90.3%). Pathological analysis disclosed pure small cell histological specimens in 24 patients (77.4%). There were no 90-day deaths. Perioperative platinum-based chemotherapy was performed in 27 patients (87.1%); adjuvant thoracic irradiation, in 7 (50%) of the 14 N+ patients; and prophylactic cranial irradiation, in 8 (29.6%) of the 27 potential candidates. Overall, disease-free and disease-specific survival rates at 5 years were 32.9 ± 10%, 35.2 ± 10% and 44.1 ± 11.3%, respectively. CONCLUSIONS: Despite the use of contemporary screening and staging methods, selection of SCLC candidates for surgery remained haphazard, surgery was typically performed in ignorance of the actual histological and adherence to treatment guidelines was inconsistent. Nevertheless, one-third of patients with SCLC who were operated on were cured, even in cases of regional or oligometastatic disease.